Lead encephalopathy presenting as status epilepticus: a case report - Iqra J. Kamal; Trevor Cerbini; Amanda Clouser; Aileen Hernandez; Diane P. Calello (BMC, 2024)
Abstract Background Lead encephalopathy, while thankfully rare, is a devastating and potentially fatal consequence of lead intoxication. Owing to successful public health measures, severe lead toxicity is not often encountered by most practicing physicians in the United States, making both its recognition and management challenging. Article summary A case study of a 4-year-old female presenting in refractory status epilepticus, found to have severe microcytic anemia and lead level > 100 mcg/dL. Case presentation We report a case of a 4-year-old girl who presented with refractory seizures, severe microcytic anemia, and a history of developmental delay who was ultimately diagnosed with lead encephalopathy, requiring multiple courses of calcium disodium ethylenediaminetetraacetic acid (EDTA) and succimer for rebounding lead levels. Conclusion Rapid recognition and appropriate management is essential to ensure neurologically intact survival. This case documents one of the first cases of successful lead chelation after multiple courses of calcium disodium EDTA and succimer dual therapy since the removal of dimercaprol from the United States market. This case also highlights the importance of using body surface area dosing for chelation therapy in order to prevent under-dosing in young children.